PERTUMBUHAN IKAN PATIN (Pangasius sp.) YANG DIPELIHARA DALAM SISTEM RESIRKULASI Growth of Catfish (Pangasius sp.) That are Kept in Recirculation System - Agung Maulana Putra; Eriyusni Eriyusni; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Water quality is one of medium for fish farming system. This study aims to determine for growth of catfish (Pangasius sp.) with using water circulation. The component of circulation using filter of sand, fibers, zeolites, activated chalcoal, and water hyacinth (Eicchornia crassipies). The result was showed highter body weight of 6,48 g during at 56 day with water circulation. Compared of body weight non circulation system the result was lowest body weight of 4,95 g.Key Word : Pangasius, Growth, recirculation system, water quality.